Source and level of crude protein for implanted finishing steers - Milton, C.T.; Brandt, Robert T., Jr. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred medium-framed, crossbred steers (738 lb) were used to compare non-protein nitrogen to natural protein supplementation of finishing diets for implanted steers. Diets were formulate d to contain 11.5 or 13.5% crude protein and were supplemented with either urea or soybean meal. A fifth treatment of cottonseed meal supplementation (13.5% dietary crude protein) was added to evaluate differences between natural sources of rumen degradable protein. Steers were implanted with Revalor® and fed for 132 days. During the first 70 days, daily gain and feed efficiency were improved 8.8 and 6.1%, respectively, for steers supplemented with soybean meal vs urea. No difference was observed with protein level. For the entire feeding period, soybean meal increased dry matter intake 3.8% compared to urea. Protein source and level interacted on daily gain. Increasing dietary protein from 11.5 to 13.5% decreased gain by urea-fed steers 8%, whereas increasing dietary protein from 11.5 to 13.5% increased gain 6.1% for steers supplemented with soybean meal. Soybean meal improved feed efficiency 7.6% compared to urea. Protein level had no effect on feed efficiency. Steers supplemented with soybean meal had larger loineye areas than those supplemented with urea. Carcass finish, percentage of carcasses grading Choice, and yield grade were not affected by treatment . Performance and carcass traits of steers fed cottonseed meal were similar to those of steers fed soybean meal. We conclude that urea cannot meet the metabolizable protein needs of implanted finishing steers. Cottonseed meal did not differ from soybean meal as a protein source in this study.
Keywords: Beef; Finishing steers; Urea; Soybean meal; Performance